Influences of the Input Factors towards Success of An Information System Project - A'ang Subiyakto; Abd. Rahman Ahlan; Mira Kartiwi; Husni Teja Sukmana (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
This study examines the input factors that were reputed theoretically affecting the information system (IS) project success in term of the processional and causal perspectives. Adopting three of the four dimensions from the McLeod and MacDonell’s (M&M’s) classification project framework dimensions, the study is initiated by inviting the internal project stakeholders in a sampled institution. A stratified sampling then identified 130 people who experienced in the projects as the sample, contacted 90 of the samples via e-mail and  distributed the paper-based questionnaire into 40 certain people especially who are on the managerial level. A number of 62 (48%) valid responses, then were analyzed using the partial least squares-structural equation modeling  (PLS-SEM) software, i.e. SmartPLS. The significances of the whole path coefficients, the acceptances of the overall hypotheses, the relevances of the three predictors relevances, and the moderate coefficient determination of the IS project success variable may present acceptability of the proposed model for the subsequent studies.